An Analysis of Translation Techniques and Quality of Event Names in Historical Book Entitled An Outline Of American History - Ismayuni Kusumawardani (Universitas Sebelas Maret, 2019)
This research aims at mapping out categories of event names found in historical book entitled AnOutline of American History, finding translation techniques used in translating the event names and describing impact of translation techniques towards translation quality in terms of accuracy and acceptability. As the basis, besides understanding about U.S.A historical country background, the translator should have competencies in selecting and applying an appropriate translation technique in order to reduce misconception translation, since not all of readers know event names in American history. The translator needs careful consideration in translating them. The different culture and historical background might be a problem and barrier for the translator.